Impairment of sperm maturation and capacitation due to diet‐dependent cholesterol overload. (4th June 2019) - Saez, F.; Whitfield, M.; Drevet, J. R.
Abstract: Background: Lipid metabolic disorders (dyslipidemia) are constantly increasing in occidental societies and lead to the development of pathologies such as obesity, diabetes, and metabolic syndrome. It has been demonstrated that dyslipidemia can alter the reproductive function. Animal models have recently been used to show that the offspring of dyslipidemic males could also develop such pathologies and that the transgenerational transmission involved post‐testicular sperm maturation. These data targeted the essential role of male gamete epididymal maturation and its importance for the health of the offspring. Objectives: This publication summarizes in the first place experimental data obtained using a mouse model of dyslipidemia‐induced post‐testicular infertility, knockout mice for the two isoforms of the 'Liver X Receptors' ( Lxr α ; β −/− ), the major regulators of cholesterol homeostasis. The impact of a high cholesterol diet (HCD) on the protein YWHAZ (14‐3‐3 ζ or tyrosine 3‐monooxygenase/tryptophan 5‐monooxygenase activation protein Zeta) was also investigated in our model. Materials and methods: In our mouse model, when young fertile Lxr α ; β −/− males aged three months were fed four weeks with a HCD, they developed an epididymal phenotype leading to infertility. The level of sperm YWHAZ was evaluated by Western blot and its tyrosine phosphorylation state by immunoprecipitation followed by Western blot. Results: Our data revealed that sperm lipid composition and structure were altered, leading to defects of the capacitation‐associated signaling pathway. They also showed that both the level and the tyrosine phosphorylation state of YWHAZ were affected by the HCD in sperm cells from Lxr α ; β −/− males. Discussion and conclusion: YWHAZ could be a new important regulator of capacitation‐associated tyrosine phosphorylation and a marker of dyslipidemia‐induced infertility.